How many subsets does the set {1, 2, 3} have?

Answers

Answer 1
Answer: \{1;\ 2;\ 3\}\n\nsubsets:\n\{1\};\ \{2\};\ \{3\}\n\{1;2\};\ \{1;3\};\ \{2;3\}\n\{1;2;3\}\n\{\O\}\n\nAnswer:8\ subsets
Answer 2
Answer: Subsets can have zero, 1, 2, or 3 members.

Zero members . . 1 subset
1 member . . . . . 3 subsets
2 members . . . . 3 subsets
3 members . . . . 1 subset

Total . . . . . . . . . 8 subsets

Related Questions

X + 1/7 = 5/14 what is the sum of x and what are the steps?
Pwease help its just easy math
Which friend has greatee elevation & which friend is father from sea level?
What is the discriminant of the quadratic equation 2x + 5x2 = 1?
I need help,, and thanks☺

How can you use the multiplication property of equality to rewrite the equation 0.6x + 4.8 = 7.2

Answers

0.6x + 4.8 = 7.2 

0.6x=7.2-4.8 

0.6x=2.4 

x=4
answer is  06xmas4.8 divido 72  is 04

Find the ordered pair (j,k) that satisfies the equations 5j-42k=1 and 2k-j=3

Answers

Answer:

Step-by-step explanation:

To find the ordered pair (j, k) that satisfies the given equations, we can solve the system of equations simultaneously.

The equations are:

5j - 42k = 1

2k - j = 3

We can solve this system of equations using various methods, such as substitution or elimination. Here, we'll use the method of substitution:

From equation 2, we can express j in terms of k:

2k - j = 3

j = 2k - 3

Now, substitute this value of j into equation 1:

5j - 42k = 1

5(2k - 3) - 42k = 1

10k - 15 - 42k = 1

-32k - 15 = 1

-32k = 16

k = -0.5

Substitute this value of k back into equation 2 to find j:

2k - j = 3

2(-0.5) - j = 3

-1 - j = 3

j = -4

Therefore, the ordered pair (j, k) that satisfies the equations 5j - 42k = 1 and 2k - j = 3 is (-4, -0.5).

Rewrite with only sin x and cos x. (1 point)sin 2x - cos 2x


2 sinx cosx - 1 + 2 sin2x
2 sin x cos2x - 1 + 2 sin2x
2 sin x cos2x - sin x + 1 - 2 sin2x
2 sin x cos2x - 1 - 2 sin2x

Answers

Note that
sin 2x = 2 sin(x) cos(x)
cos 2x =  cos²x - sin²x = 2cos²x - 1 = 1 - 2sin²x

Therefore
sin 2x -  cos 2x
= 2 sin(x) cos(x) - (1 - 2sin²x)
= 2 sin(x) cos(x) - 1 + 2sin²x

Answer: 2 sin(x) cos(x) - 1 + 2 sin²x

Factor the trinomial below 12x^2-11x-36

Answers

The factors of the trinomial are (4x-9)(3x+4).

What is a trinomial?

A trinomial is an algebraic expression that has three non-zero terms. If three monomials are separated by addition or subtraction, then it is a trinomial.

For the given situation,

The trinomial is 12x^2-11x-36.

The given trinomial is a quadratic equation.

The quadratic equation can be factored as

12x^2-11x-36

12x^2-27x+16x-36

3x(4x-9)+4(4x-9)

(4x-9)(3x+4)

Hence we can conclude that the factors of the trinomial are (4x-9)(3x+4).

Learn more about factor the trinomial here

brainly.com/question/15611437

#SPJ2

Step-by-step explanation:

12x2 - 11x - 36

12x2 - 27x + 16x - 36

3x (4x - 9) + 4(4x - 9)

(4x - 9) and (3x + 4) are the factors

Select all that apply.Which of the following could you use to find 40% of 32?

0.4 · 32
2/5 · 32
40/100 · 32
32/40

Answers

40/100= 0.4: 0.4x=32: x= 32/0.4 x=80
the answer your looking for is 80% or 80over100 or 80

Which is greater 2/3 or 2/6

Answers

2/3 because 2/6 would equal 1/3


Find the common denominator 

2/3--->4/6

2/6--->2/6

4/6 is greater than 2/6.

2/3 is greater than 2/6.